Contemporary fashion and its impact on the shape of the sleeves in the traditional Moroccan caftan - Ali Najim AbdulAllah Al Zubeidi (Basrah Arts Journal, 2023)
The Moroccan caftan has recently occupied a large space among contemporary designers because of its great aesthetic impact in terms of shape and decoration, as well as the cultural heritage of the Arab peoples. For international designers in America, Europe and East Asia, in our research, a set of images of the traditional and contemporary caftan was used, which were analyzed visually to know the quality and size of the change that occurred in the shape of the traditional sleeve as a result of its influence on modeling and the designer’s vision. In addition, the basic measurements of the sleeve were calculated to further emphasize the importance of the change in the measurements and silhouette of the contemporary sleeve. Contemporary to find out the prediction of the future shape of the kaftan, which is a kind of prediction of the shape, design, quality of fabrics and motifs used in the future fashion industry and its impact on fashion designers and the fashion industry market In our research, the study included focusing on the traditional shape of the sleeve and knowing its basic types that are known and inherited through generations, as well as studying the contemporary shapes of the sleeve through a graphic analysis of a group of contemporary costumes for fashion designers who were inspired by the Moroccan caftan as an inspiration for fashion in contemporary clothes. In front of modernity, it has changed significantly, especially in the lower sleeve area.